歯牙腫を伴った象牙質形成性幻影細胞腫の1例 - 井上, 亮; 柏木, まりな; 渡邉, 拓磨; 渡辺, 猛寛; 井上, 史基; 白井, 陽子 (日本口腔外科学会雑誌, 2024)
Dentinogenic ghost cell tumor（DGCT）is a rare benign odontogenic neoplasm classified into intraosseous and extraosseous types. The intraosseous type has been reported to feature significant osseous invasion and a high recurrence rate. Some reported DGCTs have been associated with odontoma. We report a case of DGCT in a 12-year-old female referred to our department by a local dental clinic after a radiopaque lesion was identified in the right maxilla by panoramic radiography. Intraoral examination showed delayed eruption of the right maxillary central incisor with gingival swelling. Computed tomography demonstrated tooth-like structures within the right maxilla, surrounded by a low-density area with a well-defined boundary. The area involved the crown of the right maxillary central incisor. The clinical diagnosis was calcifying odontogenic cyst associated with odontoma; therefore, surgical enucleation was performed under general anesthesia. The enucleated specimen measured approximately 20 mm in diameter, had a solid consistency, and contained several tooth-like structures. Histopathology showed the presence of ghost cells and odontogenic epithelium resembling enamel epithelium. The histopathological diagnosis was DGCT, and the tooth-like structures were confirmed as odontoma. Three years after surgery, the patient has had no tumor recurrence. Nonetheless, close follow-up is being continued.